2022
DOI: 10.3390/diagnostics12020487
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Single-Stranded DNA Binding Protein 2 Expression Is Associated with Aggressiveness and Poor Overall Survival in Patients with Invasive Breast Carcinoma

Abstract: Background: Single-stranded DNA binding protein 2 (SSBP2) is involved in the DNA damage response and the maintenance of genome stability. Previous studies have suggested that SSBP2 has a tumor suppressor function or oncogenic function. Loss of SSBP2 expression has been reported in various tumors. However, the role of SSBP2 expression in invasive breast carcinoma has not been reported. Methods: Immunohistochemical staining for SSBP2 was performed on tissue microarrays consisting of 491 invasive breast carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…SSBP2-null mice showed an enhanced predisposition to malignancy [7], and SSBP2 was downregulated in prostate cancer and esophageal squamous cell carcinoma cell lines and inhibited tumor cell growth [8,9]. Low SSBP2 expression at the protein level has been linked to an aggressive phenotype and unfavorable prognosis in some types of solid tumors [10][11][12][13]. However, studies on glioblastoma with an SSBP2-inherited variant [14] and hepatocellular carcinoma [15] showed that high SSBP2 expression was associated with poor clinical outcomes, suggesting an oncogenic role of SSBP2.…”
Section: Introductionmentioning
confidence: 99%
“…SSBP2-null mice showed an enhanced predisposition to malignancy [7], and SSBP2 was downregulated in prostate cancer and esophageal squamous cell carcinoma cell lines and inhibited tumor cell growth [8,9]. Low SSBP2 expression at the protein level has been linked to an aggressive phenotype and unfavorable prognosis in some types of solid tumors [10][11][12][13]. However, studies on glioblastoma with an SSBP2-inherited variant [14] and hepatocellular carcinoma [15] showed that high SSBP2 expression was associated with poor clinical outcomes, suggesting an oncogenic role of SSBP2.…”
Section: Introductionmentioning
confidence: 99%